2008
DOI: 10.1093/humupd/dmn055
|View full text |Cite
|
Sign up to set email alerts
|

New insights into epididymal biology and function

Abstract: Significant progress has been made in our understanding of epididymal function providing new insights that ultimately could improve human health. The data also indicate that the human epididymis plays an important role in sperm maturation but has unique properties compared with animal models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
455
0
28

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 509 publications
(520 citation statements)
references
References 140 publications
10
455
0
28
Order By: Relevance
“…Our preliminary results using epididymal sperm indicated that the currents we recorded in testicular sperm in this work were similar. Initially, total whole-cell currents were recorded using the following solutions: external solution (in mM): 118 Na-MetSO 4 CHO Cell TRPM8 Flexstation II Assay. CRISP4 CRISP domain antagonism of TRPM8 was tested in CHO cells expressing HA-tagged TRPM8 using a fluorometric plate assay.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our preliminary results using epididymal sperm indicated that the currents we recorded in testicular sperm in this work were similar. Initially, total whole-cell currents were recorded using the following solutions: external solution (in mM): 118 Na-MetSO 4 CHO Cell TRPM8 Flexstation II Assay. CRISP4 CRISP domain antagonism of TRPM8 was tested in CHO cells expressing HA-tagged TRPM8 using a fluorometric plate assay.…”
Section: Methodsmentioning
confidence: 99%
“…Male fertility is dependent upon successful spermatogenesis within the testis and two phases of posttesticular sperm maturation, known as epididymal maturation and capacitation (2). Epididymal maturation involves, among other processes, protein absorption onto the sperm membrane, and the establishment of ionic gradients (3,4). Capacitation normally occurs in the female reproductive tract and broadly involves the shedding of proteins, membrane reorganization, changes in ion permeability, and the activation of signal transduction pathways.…”
mentioning
confidence: 99%
“…(r = 0.48 to 0.57). In the present study, correlations between testosterone and gonad size are likely related to the dependence of testis growth and epididymal development upon androgens (AMANN; WALKER, 1983;CORNWALL, 2009;CHENG et al, 2010;ROBAIRE;HAMZEH, 2011) but these correlations were more significant for GnRH-stimulated than for basal testosterone. As well established, testosterone is dependent on both GnRH and LH, and its secretion occurs in pulses (BRIDGES et al, 1993;BAGU et al, 2006).…”
Section: Resultsmentioning
confidence: 48%
“…Our findings suggest that the development of epididymis is closely linked to that of the gonad and to events of spermatogenesis. In fact, studies have pointed out that epididymal function not only depends on androgens but also on the influence of luminal components (such as growth factors) from the testis (ABE; TAKANO; ITO, 1984;CORNWALL, 2009 The number of tubules with either round, elongate or mature spermatids quantified at 30 mo. was correlated with sperm progressive motility and vigor evaluated from 25 to 29 mo.…”
Section: Resultsmentioning
confidence: 99%
“…La maturation post-testiculaire des spermatozoïdes recouvre un ensemble de processus complexes qui vont progressivement modifier structurellement et fonctionnellement les gamètes en transit et ainsi leur conférer leurs aptitudes fécondantes, c'est-à-dire l'expression de leur motilité et la capacité à reconnaître la zone pellucide de l'ovule et à fusionner avec ce dernier. L'épithélium composite pseudostratifié du tubule épididymaire assure ces rôles essentiellement grâce à ses multiples activités de sécrétion et de réabsorption qui changent localement et séquentiellement la composition du fluide épididymaire dans lequel baignent les gamètes (pour une revue récente voir [4]). Une expérience simple qui illustre l'importance de ce tissu dans la fertilité mâle chez les mammifères consiste à tester les capacités fécondantes de gamètes prélevés dans différentes régions du tubule Un couple sur six dans le monde consulte en raison de difficultés à concevoir.…”
unclassified